Transparency in empirical economic research - Cristina Blanco-Perez; Abel Brodeur (IZA World of Labor, 2019)
The open science and research transparency movement aims to make the research process more visible and to strengthen the credibility of results. Examples of open research practices include open data, pre-registration, and replication. Open science proponents argue that making data and codes publicly available enables researchers to evaluate the truth of a claim and improve its credibility. Opponents often counter that replications are costly and that open science efforts are not always rewarded with publication of results.
Keywords: A11; C13; C44; I10; 330; research transparency; open science; data sharing; p-hacking and replication